2017
DOI: 10.1111/jfs.12389
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Corduk (Echinophora tenuifolia subsp. sibthorpiana) on safety and quality of kofte, a Turkish style meatball

Abstract: In this research, the effect of Echinophora tenuifolia subsp. sibthorpiana (Corduk) on the inactivation of Salmonella Typhimurium in kofte (Turkish style meatball) was evaluated; as well as the quality characteristics of kofte (proximate composition, oxidation level, color parameters, microbiological, and sensory properties), during storage period at 4 8C for 7 days. Using Corduk at concentrations of 0.5, 1, and 1.5% in kofte was reduced the number of Salmonella cells in the range of 0.35-1.0 log cfu/g. The lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…As natural antimicrobials and natural antioxidants, natural plant extracts have the potential to enhance the entire quality of meat products [ 8 , 37 , 38 ]. Cordeuk with concentrations of 0.5–1.5% could result in 0.35–1.0 log CFU/g reductions in S. Typhimurium in Turkish-style meatballs [ 39 ]. Similarly, Xing et al [ 29 ] found that 80 mg/mL of Chrysanthemum buds’ crude extract could reduce approximately 1-log CFU/g of S. Typhimurium in cooked chicken.…”
Section: Resultsmentioning
confidence: 99%
“…As natural antimicrobials and natural antioxidants, natural plant extracts have the potential to enhance the entire quality of meat products [ 8 , 37 , 38 ]. Cordeuk with concentrations of 0.5–1.5% could result in 0.35–1.0 log CFU/g reductions in S. Typhimurium in Turkish-style meatballs [ 39 ]. Similarly, Xing et al [ 29 ] found that 80 mg/mL of Chrysanthemum buds’ crude extract could reduce approximately 1-log CFU/g of S. Typhimurium in cooked chicken.…”
Section: Resultsmentioning
confidence: 99%
“…Pickling herb (Echinophora tenuifolia L.) or PHET, is a commonly found herb in Turkey. It is also known as 'Çörtük otu', 'Turşu otu' and 'Tarhana otu' (Gokbulut et al, 2013;Sengun et al, 2018). Due to its pleasant smell and antifungal effects, fresh or dried leaves of PHET were used in different foods including pickles and meatballs (Sengun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known as 'Çörtük otu', 'Turşu otu' and 'Tarhana otu' (Gokbulut et al, 2013;Sengun et al, 2018). Due to its pleasant smell and antifungal effects, fresh or dried leaves of PHET were used in different foods including pickles and meatballs (Sengun et al, 2018). In addition to other properties, such ingredients including PHET may improve different functional properties of food products.…”
Section: Introductionmentioning
confidence: 99%